Construindo uma pedagogia a partir de vivências: reflexões sobre minha trajetória e a importância da educação socioemocional - Pontes, Samantha de Oliveira Carmo (Universidade Federal de São Carlos, 2022)
This conclusion work is defined as a memorial, which aimsto rescue memories of my childhood and adolescence, as well as my adulthood, combining my individual personal growth with the environment which I was provided with, as well as the importance of my family and friends in this path. In line with studies from the cultural-historical theory, and studies in the field of neuroscience and social-emotional education, I seek to add meaning to the theoretical foundation of my own history and to propose a more humane education that considers emotions, the stages of child development, and that has as main goal to educate children in their entirety. The work develops itself from a temporal perspective, in which I start by describing my childhood and adolescence, through my studying years at the university until my moving to another country, in which I detail my personal and professional growth, trying and seeking answers to many challenges found throughout my pedagogical work with small children.
Building a pedagogy based on experiences: reflections about my trajectory and the importance of socioemotional education
Keywords: Memorial de formação; Teoria histórico cultural; Educação sócio emocional; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM